Some New Inequalities of Jordan Type for Sine - Shan-Peng Zeng; Yue-Sheng Wu (The Scientific World Journal)
The authors find some new inequalities of Jordan type for the sine function. These newly established inequalities are of new form and are applied to deduce some known results.